Penerapan Pembuatan Teknik Lubang Biopori Resapan Sebagai Upaya Pengendalian Banjir - Yohana, Corry; Griandini, Dientje; Muzambeq, Said (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
The students of State University of Jakarta (UNJ) try to apply the bio pore hole technique to restraint the flood problem through the community service program. The purpose of this program is (1) sharing knowledge to campus community about application of science and technology, (2) adding skill to general community especially the college student of UNJ in using bio pore holes technique to avoid the flood problem, (3) Improving the image of UNJ as a supplier of versatile functional technology to the developing regions. The method that have been used for this community service program are lecturing, discussing and direct practicing after material delivery through individual and groups.